The Relationship between Emotional Schemas and Uncertainty Intolerance with the Mediating Role of Experiential Avoidance in Women - Sara Abdollahpour; Fateme Dehghani-Arani; Hojjatollah Farahani (پژوهش‌های کاربردی روانشناختی)
The purpose of the present study was to ascertain the relationship between Emotional Schemas and Uncertainty Intolerance in women, with Experiential Avoidance serving as a mediator. The research method employed was descriptive, and the study was of the correlational type, utilizing structural equation modeling to predict. The statistical population included all women over 20 years old living in the Tehran province in 2023, had no experience of divorce and had academic education, and 221 of them were selected through a purposive sampling method. Purposive sampling was employed to select 221 of these women. The Leahy Emotional Schemas Scale (LESS), Intolerance of Uncertainty questionnaire (IUS), and Experimental Avoidance questionnaire (AAQ-II) were the measurement instruments used to assess the variables of the research. After the participants completed the questionnaires, the data were analyzed using structural equation modeling and the AMOS-20 and SPSS-24 software. The final model demonstrated a satisfactory fit, as indicated by the results. As per the results, the Experimental Avoidance variable serves as a mediating variable in the relationship between Intolerance of Uncertainty and Emotional-Adaptive and Emotional-Maladaptive Schemas, and both effects are statistically significant (P<0.05). As a result, Experimental Avoidance had a 67% impact on the relationship between Intolerance of Uncertainty and Emotional-Adaptive Schema of women and a 22.3% effect on the relationship between Intolerance of Uncertainty and Emotional-Adaptive Schema of women. Therefore, it is evident that Experiential Avoidance influences the relationship between Intolerance of Uncertainty and the emotional schemas of women. Consequently, it is imperative that mental health professionals implement strategies to mitigate women's Experiential Avoidance.